Ultrashort-Pulse Lasers Treating the Crystalline Lens: Will They Cause Vision-Threatening Cataract? (An American Ophthalmological Society Thesis) - Krueger, Ronald R. (The American Ophthalmological Society, 2012)
PURPOSE: To demonstrate that ultrashort-pulse laser treatment in the crystalline lens does not form a focal, progressive, or vision-threatening cataract. METHODS: An Nd:vanadate picosecond laser (10 ps) with prototype delivery system was used. Primates: 11 rhesus monkey eyes were prospectively treated at the University of Wisconsin (energy 25–45 μJ/pulse and 2.0–11.3M pulses per lens). Analysis of lens clarity and fundus imaging was assessed postoperatively for up to 4½ years (5 eyes). Humans: 80 presbyopic patients were prospectively treated in one eye at the Asian Eye Institute in the Philippines (energy 10 μJ/pulse and 0.45–1.45M pulses per lens). Analysis of lens clarity, best-corrected visual acuity, and subjective symptoms was performed at 1 month, prior to elective lens extraction. RESULTS: Bubbles were immediately seen, with resolution within the first 24 to 48 hours. Afterwards, the laser pattern could be seen with faint, noncoalescing, pinpoint micro-opacities in both primate and human eyes. In primates, long-term follow-up at 4½ years showed no focal or progressive cataract, except in 2 eyes with preexisting cataract. In humans, <25% of patients with central sparing (0.75 and 1.0 mm radius) lost 2 or more lines of best spectacle-corrected visual acuity at 1 month, and >70% reported acceptable or better distance vision and no or mild symptoms. Meanwhile, >70% without sparing (0 and 0.5 mm radius) lost 2 or more lines, and most reported poor or severe vision and symptoms. CONCLUSIONS: Focal, progressive, and vision-threatening cataracts can be avoided by lowering the laser energy, avoiding prior cataract, and sparing the center of the lens.